A Printable Metallic Current Collector for All‐Printed High‐Voltage Micro‐Supercapacitors: Instantaneous Surface Passivation by Flash‐Light‐Sintering Reaction. (30th April 2020) - Chae, Changju; Han, Jae Hee; Lee, Sun Sook; Choi, Youngmin; Kim, Tae‐Ho; Jeong, Sunho
Abstract: Recently, a printable power source that can be implemented on demand in integrated circuitries has gained tremendous attention to facilitate next‐generation, form‐factor free, miniaturized electronic systems. Among various energy storage units, a solid‐state micro‐supercapacitor with in‐plane device architecture has been recognized as a viable candidate with characteristic advantages of long cycle life‐time, high frequency response, and fast charge/discharge rate. However, to date, high performance, all‐printed micro‐supercapacitors have rarely been reported owing to an absence of printable current collector materials that can sustain high voltage conditions. In this study, a multidimensional printable particle mixture comprising Ni nanoparticles, Ni flakes, and a photoreactive polymer, polyvinylpyrrolidone is proposed. The highly conductive, printed metallic current collector is generated with a conductive surface passivation layer in a timescale of 10 −3 s by flash‐light sintering process. It is revealed that the resulting metallic current collector is stable at a voltage as high as 3 V in the carbon electrode‐based device, enabling the fabrication of an all‐printed solid‐state micro‐supercapacitor with an areal energy density of 79–23 mJ cm −2 at an areal power density of 0.4–12.8 mW cm −2 . Arbitrarily designed device circuits can be generated on demand simply by using a digitally programmable printing process, without incorporation of additional interconnection lines. Abstract : A printable metallic current collector for all‐printed, solid‐state micro‐supercapacitors is proposed by using a multidimensional printable particle mixture and flash‐light sintering technique. It is revealed that the resulting metallic current collector is stable at a voltage condition as high as 3 V in carbon electrode‐based devices, enabling an areal energy density of 79–23 mJ cm −2 at an areal power density of 0.4–12.8 mW cm −2 .